Genetic Architecture of Reciprocal CNVs - Golzio, Christelle (2013)
Copy number variants (CNVs) represent a frequent type of lesion in human genetic disorders that typically affects numerous genes simultaneously. This has raised the challenge of understanding which genes within a CNV drive clinical phenotypes. Although CNVs can arise by multiple mechanisms, a subset is driven by local genomic architecture permissive to recombination events that can lead to both deletions and duplications. Phenotypic analyses of patients with such reciprocal CNVs have revealed instances in which the phenotype is either identical or mirrored; strikingly, molecular studies have revealed that such phenotypes are often driven by reciprocal dosage defects of the same transcript. Here we explore how these observations can help the dissection of CNVs and inform the genetic architecture of CNV-induced disorders.